Science process skills of prospective science teachers' in practicum activity at the laboratory - Wola, Brian Ricard; Rungkat, Jovialine Albertine; Harindah, Gerry Michael Donad (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2023)
This research aims to determine the prospective science teachers' mastery level of science process skills (SPS), the mastery level of SPS indicators, and the prospective science teachers' mastery level of SPS based on gender. This study used a descriptive method with a quantitative approach. Purposive sampling techniques are used and obtain 23 prospective science teachers during the last two years at the Universitas Negeri Manado. The research instrument used interview guidelines and observation sheets. The results showed (1) the prospective science teachers' mastery level of SPS in practicum activity at the laboratory is 80% categorized as sufficient; (2) the mastery level of SPS indicators by prospective science teachers: classifying 87% categorized as good, observing 86% categorized as good, asking questions 82% categorized as sufficient, experimenting 81% categorized as sufficient, planning an experiment 79% categorized as sufficient, interpreting data 77% categorized as sufficient, and communicating 70% categorized as very poor; (3) based on gender, the mastery level of the SPS by prospective female science teachers (83%) is higher than prospective male science teachers (73%). The findings are useful for science education lecturers to direct their laboratory teaching for prospective science teachers to master science process skills.